Swiprosin-1/EFhd2 controls B cell receptor signaling through the assembly of the B cell receptor, Syk, and phospholipase C gamma2 in membrane rafts. - Kroczek, C; Lang, C; Brachs, S; Grohmann, M; Dütting, S; Schweizer, A; Nitschke, L; Feller, S; Jäck, H; Mielenz, D (2010)
Compartmentalization of the BCR in membrane rafts is important for its signaling capacity. Swiprosin-1/EFhd2 (Swip-1) is an EF-hand and coiled-coil-containing adaptor protein with predicted Src homology 3 (SH3) binding sites that we identified in membrane rafts. We showed previously that Swip-1 amplifies BCR-induced apoptosis; however, the mechanism of this amplification was unknown. To address this question, we overexpressed Swip-1 and found that Swip-1 amplified the BCR-induced calcium flux in WEHI231, B62.1, and Bal17 cells. Conversely, the BCR-elicited calcium flux was strongly attenuated in Swip-1-silenced WEHI231 cells, and this was due to a decreased calcium mobilization from intracellular stores. Complementation of Swip-1 expression in Swip-1-silenced WEHI231 cells restored the BCR-induced calcium flux and enhanced spleen tyrosine kinase (Syk) tyrosine phosphorylation and activity as well as SLP65/BLNK/BASH and phospholipase C gamma2 (PLCgamma2) tyrosine phosphorylation. Furthermore, Swip-1 induced the constitutive association of the BCR itself, Syk, and PLCgamma2 with membrane rafts. Concomitantly, Swip-1 stabilized the association of BCR with tyrosine-phosphorylated proteins, specifically Syk and PLCgamma2, and enhanced the constitutive interaction of Syk and PLCgamma2 with Lyn. Interestingly, Swip-1 bound to the rSH3 domains of the Src kinases Lyn and Fgr, as well as to that of PLCgamma. Deletion of the predicted SH3-binding region in Swip-1 diminished its association and that of Syk and PLCgamma2 with membrane rafts, reduced its interaction with the SH3 domain of PLCgamma, and diminished the BCR-induced calcium flux. Hence, Swip-1 provides a membrane scaffold that is required for the Syk-, SLP-65-, and PLCgamma2-dependent BCR-induced calcium flux.